Statistical analysis from a Gender perspective (Journal Of Educational and Psychological Researches, 2022)
This research is a theoretical study that deals with the presentation of the literature of statistical analysis from the perspective of gender or what is called Engendering Statistics. The researcher relied on a number of UN reports as well as some foreign sources to conduct the current study. Gender statistics are defined as statistics that reflect the differences and inequality of the status of women and men overall domains of life, and their importance stems from the fact that it is an important tool in promoting equality as a necessity for the process of sustainable development and the formulation of national and effective development policies and programs. The empowerment of women and the achievement of equality between men and women is a matter of human rights, and should not be seen as an only women case, this is the only way to build a sustainable and developed society. The empowerment of women and equality between men and women are prerequisites for achieving political, social, economic, cultural and environmental security among all individuals and people. The success of any policy depends on the strength of the constants and the foundations on which they have been based. The desired developmental results are mostly due to the inaccuracy of the data on which the strategy was based or to neglect the needs of different social groups at the planning stage. The research concluded with a number of conclusions, proposals, and recommendations.